2013
DOI: 10.1159/000355310
|View full text |Cite
|
Sign up to set email alerts
|

Do Women Live Longer or Do Men Die Earlier? Reflections on the Causes of Sex Differences in Life Expectancy

Abstract: Background: Although many different factors have been identified to contribute to excess male mortality, it is still unclear which path of the complex cause-effect chain is the decisive driver of the life expectancy gap between women and men. Objective: The question behind this study is whether these sex differences are caused primarily by factors leading to low female mortality or rather by factors causing high male mortality. We hypothesise that they are to a large extent caused by specific subpopulations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 31 publications
(44 reference statements)
4
51
1
3
Order By: Relevance
“…The majority of research into gender differences in survival has focused upon younger to middle aged populations, with few studies including older people in general (5,6,7), and even fewer studies among the oldest old. (8) Literature that does exist among older people is often contradictory. Findings from some cross-sectional studies have suggested a convergence of differences in comorbidity between the genders in several areas of health, function and disease among the oldest old (9).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of research into gender differences in survival has focused upon younger to middle aged populations, with few studies including older people in general (5,6,7), and even fewer studies among the oldest old. (8) Literature that does exist among older people is often contradictory. Findings from some cross-sectional studies have suggested a convergence of differences in comorbidity between the genders in several areas of health, function and disease among the oldest old (9).…”
Section: Introductionmentioning
confidence: 99%
“…The gender gap in life expectancy is a well-known fact in demography, with female life expectancy exceeding that of males (Waldron 2000;Luy and Gast 2014;Caselli et al 2014). Research on gender differences in mortality and morbidity has mainly focused on older people (Bardage et al 2005), but our study provides evidence that women evaluate their health worse than men already in young and middle adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous research, females might live longer as a result of disproportionately high mortality levels in males (Ginter and Simko 2013;Luy and Gast 2014). Sex differences in diet, iron status, and hormone levels can affect the absorption of elements (Kazi et al 2008;Olsson et al 2002).…”
Section: Individual Factors Influencing Element Concentrations In Cenmentioning
confidence: 96%